2017
DOI: 10.1016/j.colsurfb.2017.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt and titanium nanoparticles influence on mesenchymal stem cell elasticity and turgidity

Abstract: Bone cells are damaged by wear particles originating from total joint replacement implants. We investigated Mesenchymal stem cells (MSCs) nanomechanical properties when exposed to cobalt and titanium nanoparticles (resembling wear debris) of different sizes for up to 3days using AFM nanoindentation; along with flow-cytometry and MTT assay. The results demonstrated that cells exposed to increasing concentrations of nanoparticles had a lower value of elasticity and spring constant without significant effect on c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 53 publications
1
14
0
Order By: Relevance
“…Moreover, particles concentrations used in this study were the same range as studies and found in patient tissues [29], [35]. Moreover, no difference between Ti oxides and Ti elemental nanoparticles was found on the mitochondrial activity and mechanical properties of cells; [36], [37] similarly, Co oxide had the same effects as elemental Co [38]. Therefore the experimental conditions closely resemble in vivo situations.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Moreover, particles concentrations used in this study were the same range as studies and found in patient tissues [29], [35]. Moreover, no difference between Ti oxides and Ti elemental nanoparticles was found on the mitochondrial activity and mechanical properties of cells; [36], [37] similarly, Co oxide had the same effects as elemental Co [38]. Therefore the experimental conditions closely resemble in vivo situations.…”
Section: Discussionsupporting
confidence: 60%
“…It is believed that cytoskeleton is the main component of sensing mechanical changes [51], [55], [56]. Even though wear particles may not impact cell viability directly, they induce other mitochondrial and structural changes in the cells they affect as the cascade of event subsequent to exposure to metal wear debris can be potentially deleterious to the long life of implanted joint replacement devices as shown here [36], [37]. Little to no change was observed in the MTT viability results for Saos-2 cells for both Cobalt and Titanium nanoparticle exposure (Figure 1), even though the same sized particles of Cobalt had a greater impact on the viability of the mouse MC3T3-E1 and cells [44], [37].…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Although the majority of research on PPOL has concentrated on cells of the monocyte/macrophage/foreign body giant cell/osteoclast lineage, other cells in the BMU, as well as fibroblasts, vascular progenitors and others play prominent roles in the development of PPOL. Previous research has documented adverse effects of different byproducts of wear on osteoblasts [15,84,106,[112][113][114], osteocytes [83,84,115], and mesenchymal stem cells and osteoblast progenitors [116][117][118]. In general, chronic inflammation associated with byproducts of wear suppresses bone formation by inhibiting the proliferation, differentiation, maturation and function of progenitor cells and their downstream lineage cells.…”
Section: The Implant-bone Interface: a Series Of Bone Multicellular Umentioning
confidence: 99%
“…Moreover, the interest in the synthesis of biomimetic materials (e.g., synthetic skins [10], artificial cell systems [11], and nanotextured implants [12] and functional particles [13]) has demonstrated nanoindentation as the ideal method for probing local gradients and heterogeneities in natural materials and for examining their hierarchical and multiscale organization. Nanoindentation can therefore be expected to be a very useful method in the evolving field of bio-based polymer nanocomposite systems that serve to replace oil-based polymers with polymers partially or totally obtained from renewable resources because these systems often exhibit novel unexplored material interactions at the surface of the nanophase.…”
Section: Introductionmentioning
confidence: 99%